Enhancing magnetic and electrochemical properties of cobalt modified ZnS nanoparticles: A facile synthesis approach - Pawan Kumar Pathak; Devendra Kumar; Santosh J. Uke; Amit Kumar Singh; Manika Chaudhary; Neha V. Brahmankar; Subodh Kumar Sharma; Beer Pal Singh; Ashwani Kumar (Next Nanotechnology)
In this investigation, we effectively fabricated zinc sulphide (ZnS) nanoparticles doped with cobalt (Co) using the facial synthesis method at different concentrations (3 %, 6 %, and 9 %). The Co doping-dependent structural, morphological, magnetic, optical, and electrochemical properties of the ZnS nanostructures were systematically explored. The analysis of magnetic properties revealed that the ferromagnetic ZnS nanoparticles exhibited superparamagnetic behaviour, showing an increased magnetization with higher Co doping content. Electrochemical assessments of the electrodes were conducted in 1 mol L−1 Na2SO4 liquid electrolyte. The 3 % Co doped ZnS variant, which demonstrated the highest energy density (14.27 Whkg−1) at 10 mAcm−2 and capacity retention (94.76 %) after 2000 cycles at 50 mAcm−2. Further, a trend of a decrease in specific capacitances and energy density with an increase in Co doping is observed. This outcome implies that optimal levels of Co doping can enhance the electrochemical and magnetic performances of ZnS nanoparticles, underscoring their potential for applications in energy storage.